The Franciscans in Cathay: memory of men and places. A Contribution for the genealogy of geographical knowledge of Alexander von Humboldt - Buffon, Giuseppe (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2015)
SummaryThe study analyzes the process that leads to the elaboration of the thesis of a continuity between the Medieval Asia mission and the New World mission. This effort, undertaken by the Catholic historiography of the mission during the XIX century, is the result of the impulse provided by Alexander von Humboldt’s studies about the discovery of America (Examen critique). The data about the geography of Asia collected by the missionaries-travelers working in the territory between Karakorum and Khanbalik during the XIII e XIV century reaches Christopher Colombus with the mediation of Roger Bacon, whom Humboldt himself esteems as a true cultural mediator. The conclusion of the article tries to identify reasons and modalities of the secularization of the missionary concept, i.e. the shift from the ideal of the propagation of the Christian message to a prevailing interest for cartography and topography, transformations arranged by a late medieval historiography that introduces into martyrolagia the loca toponomastica. SommarioLo studio analizza il processo che conduce all’elaborazione della tesi di una continuità tra missione asiatica medievale e missione nel Nuovo Mondo. L’impegno, assunto dalla storiografia missionaria cattolica lungo il corso del XIX secolo, costituisce l’esito dell’impulso proveniente dagli studi svolti da Alexander von Humboldt intorno all’esplorazione delle Americhe (Examen critique). Le informazioni sullo spazio asiatico trasmesse dai missionari operanti durante il XIII e il XIV secolo tra Karakorum e Khanbaliq pervengono a Cristoforo Colombo mediante Ruggero Bacone (Opus majus), che Humlbodt stesso stima mediatore culturale per antonomasia. La parte conclusiva della ricerca si occupa di stabilire modalità e ragioni della secolarizzazione del concetto di missione, cioè del trasferimento all’interesse cartografico dell’anelito alla propagazione del messaggio cristiano fino agli estremi confini della terra, trasformazione predisposta dalla storiografia medievale che nei martirologia inserisce appunto i loca toponomastici. ResumenEl estudio analiza el proceso que conduce a la elaboración de la tesis sobre una posible continuidad entre la misión asiática medieval y la misión en el Nuevo Mundo. El empeño, asumido por parte de la historiografía misionera católica a lo largo del siglo XIX, constituye el resultado del impulso proveniente de los estudios desarrollados por Alexander von Humboldt en torno a la exploración de las Américas (Examen critique). Las informaciones sobre el espacio asiático transmitidas por los misioneros que operaron durante los siglos XIII y XIV entre Karakorum y Khanbaliq llegan a Cristobal Colón a través de Roger Bacon (Opus majus), que el mismo Humboldt considera como un mediador cultural por antonomasia. La parte conclusiva de la investigación se dedica a establecer las modalidades y regiones de la secularización del concepto de misión, es decir, de la transferencia al interés cartográfico del anhelo por la propagación del mensaje cristiano hasta los extremos confines de la tierra, una transformación que fue predispuesta por la historiografía medieval que en los martirologios insertaba los lugares toponímicos.